Comparison of caloric expenditure and heart frequency in women in the presence and virtual zumba classes (Research, Society and Development, 2021)
The present study compared caloric expenditure and variation in women in face-to-face and virtual zumba classes. It was an exploratory, descriptive and cross-sectional, quantitative study. The sample consisted of ten women, with an average age of 36 (± 4.7) years, who participated in two zumba classes, one in person and one virtual. The instruments used for the collection were a sociodemographic questionnaire, a frequency meter, a television and an Xbox 360. The data collected were analyzed using the statistical program SPSS 24.0. The results showed that there was no statistically significant difference in relation to caloric expenditure, when comparing the two types of zumba classes (p = 0.221). However, there was a statistically significant difference in relation to the average heart rate, with the classroom class having the highest index (p = 0.005). Therefore, when comparing the two modes of zumba classes, face-to-face and virtual, the study revealed that there was no difference in terms of caloric expenditure in these classes. However, the intensity of the face-to-face class remained more intense and uniform, evidenced by the superiority in the values of FCmed, in the face-to-face class.